Bimbingan Teknis Pengolahan Wedang Penambah Imunitas Desa Kawedusan Kecamatan Plosoklaten Kabupaten Kediri - Agustia Dwi Pamujiati; Tjatur Prijo Rahardjo; Ahmad Iksan Nudin; Andan Diyah Wulan (Kadiri University, 2022)
There are various types of herbal plants in Indonesia, such as ginger, turmeric, lemongrass, cardamom, cloves, cinnamon, star anise, and others. Each herbal plant contains various bioactive compounds that have antioxidant activity. Antioxidants can function to increase immunity. The immunity of the residents of Kawedusan Village decreased during the transition period which was marked by many people experiencing symptoms of cough, runny nose, and fever. Due to this phenomenon, it is necessary to conduct training to manufacture immunity-enhancing drinks made from various herbal plants. Community service was carried out for two months starting from January to March 2022 in Sadon Hamlet, Kawedusan Village, Plosoklaten District, Kediri Regency. This community service employed three methods: the preparation stage, lectures, and field practice. The ingredients used in making an immunity-boosting drink include lemongrass, turmeric, ginger, cinnamon, rock sugar, lime, and honey. Community service activities for the manufacture of an immunity-boosting drink were successful and valuable. The Kawedusan Village apparatus supports the activity and the participated residents were highly enthusiasticÂ Tumbuhan herbal di Indonesia beragam jenisnya seperti jahe, kunyit, sereh, kapulaga, cengkeh, kayu manis, bunga lawang, dan sebagainya. Setiap tumbuhan herbal mengandung senyawa bioaktif beragam yang memiliki aktivitas sebagai antioksidan. Antioksidan dapat berfungsi untuk meningkatkan imunitas. Imunitas warga Desa Kawedusan mengalami penurunan di masa pancaroba yang ditandai dengan banyaknya orang yang mengalami gejala batuk, pilek, dan demam. Adanya fenomena tersebut maka perlu dilakukan pelatihan pembuatan wedang penambah imunitas dari bermacam-macam tumbuhan herbal. Pengabdian kepada masyarakat dilakukan selama 2 bulan mulai bulan Januari hingga Maret 2022 di Dusun Sadon Desa Kawedusan Kecamatan Plosoklaten Kabupaten Kediri. Pengabdian kepada masyarakat ini menggunakan 3 metode yaitu tahap persiapan, ceramah, dan praktek lapang. Bahan yang digunakan dalam pembuatan wedang penambah imunitas antara lain batang sereh, kunyit, jahe, kayu manis, gula batu, jeruk nipis, dan madu. Kegiatan pengabdian kepada masyarakat pembuatan wedang penambah imunitas berjalan dengan sukses bermanfaat. Perangkat Desa Kawedusan mendukung kegiatan ini dan antusiame warga sangat tinggi.Â